Chemical Characteristics and Antioxidant Activity of Fish Skin Collagen: Review - Sabela, Bendi; Ramadhini, Tri Karimah (Universitas Serambi Mekkah, 2025)
Fish skin is a fishery waste product with a high collagen content. This review aims to compile and summarize the latest data on the chemical characteristics and antioxidant activity of fish skin collagen. Fish skin collagen can be extracted using acid, enzymatic, ultrasound, and deep eutectic solvent (DES) methods. The yield of fish skin collagen ranges from 2.2 to 61.5%. The proximate content of fish skin collagen is 36.64–77.5% protein; 0.28–30.43% lipids; 0.43–49.25% ash; and 0.061–10.25% moisture. The most dominant amino acid in fish skin collagen is glycine. The composition of fish skin collagen includes carbon, oxygen, silicon, chlorine, sodium, magnesium, phosphorus, sulfur, potassium, and iron. Fish skin collagen shows antioxidant activity with ABTS (2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid), DPPH (2,2-diphenyl-1-picrylhydrazyl), ORAC (oxygen radical absorbance capacity), FRAP (ferric reducing antioxidant power), OH radical scavenging, and NO radical scavenging methods. The antioxidant activity of fish skin collagen in the DPPH free radical scavenging method is 39.57–40.89%.